Use of NMR and Other Spectroscopy Techniques in Heterocyclic Oxadiazole Derivatives Studies: A Review - Neha Sahu (International Journal of Photochemistry and Photochemical Research, 2024)
It was possible to create a number of novel symmetrical 2,5-dialkyl-1,3,4-oxadiazoles with substituents including carboxymethylamino, isopropyloxycarbonylmethylamino, and bromine at the terminal positions of the alkyl groups. The multistep process that was devised used hydrazine hydrate, phosphorus oxychloride, and commercially available acid chlorides that varied in alkyl chain length and terminal substituent.Diisopropyliminodiacetate was an easy way to substitute the intermediate bromine-containing 2,5-dialkyl-1,3,4-oxadiazoles. This was followed by hydrolysis in an aqueous methanol solution, which produced the corresponding 1,3,4-oxadiazoles with carboxymethylamino substituents. All of the products' structures were verified using standard spectroscopic techniques such 1H NMR, 13C NMR, and HRMS. One of the most significant heterocyclic fragments and a potential building block for drug discovery is the 1,3,4-oxadiazole scaffold. Substituted 1,3,4-oxadiazoles exhibit a wide range of pharmacological properties, including antitubercular, anticancer, anti-inflammatory, antibacterial, antiviral, antifungal, insecticidal, antioxidant, and analgesic effects. Additionally, licensed medications such as the antiviral drug Raltegravir, the anticancer drug Zibotentan, and the antihypertensive drugs Tiodazosin and Nesapidil contain the 1,3,4-oxadiazole core. This review compiles the primary methods for determining potential avenues for structural modification and pharmacological activity of non- condensed heterocyclic systems based on the 1,3,4-oxadiazole ring, highlighting their promise as targets in contemporary bioorganic and medicinal chemistry.
Keywords: 1,3,4-oxadiazoles; Heterocycles; organic ligands; spectral characterization; substitution